A study on combination of daptomycin with selected antimicrobial agents: in vitro synergistic effect of MIC value of 1 mg/L against MRSA strains - Lee, Yi-Chien (BMC Pharmacol Toxicol, 2019)
BACKGROUND: Daptomycin is an important drug used in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infection. A high dose of daptomycin is indicated for an MRSA infection with a minimum inhibitory concentration (MIC) of 1 mg/L for daptomycin. Combination therapies with daptomycin and other antimicrobial agents, including fosfomycin, display in vitro synergism potentially. This study was conducted to investigate the in vitro synergistic effect of daptomycin-based combination therapy against MRSA strains with high daptomycin MIC. METHOD: The synergistic effects of daptomycin in combination with fosfomycin, gentamicin, linezolid, oxacillin, or rifampicin against MRSA with an MIC of 1 mg/L for daptomycin were measured using the microbroth checkerboard assay in vitro. RESULT: A total of 100 MRSA isolates was tested. The synergistic interactions of the drugs were evaluated using the fractional inhibitory concentration index. The MIC values revealed that all isolates (100%) were found to be susceptible to linezolid, 85% to fosfomycin, 8% to gentamicin, 69% to rifampicin, and no isolate was susceptible to oxacillin. The in vitro synergism rates of daptomycin in combination with fosfomycin, oxacillin, gentamicin, linezolid, and rifampicin were 37, 11, 5, 3, and 1%, respectively. CONCLUSION: The combination of daptomycin plus fosfomycin may be an effective therapeutic option for MRSA infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40360-019-0305-y) contains supplementary material, which is available to authorized users.